Membangun Kembali Animo Wisata Akibat Pandemi Melalui Signage & Katalog Wisata DIGITAL - Retno Purwanti Murdaningsih; Yunisa Fitri Andriani; Zita Nadia (Jurnal Abdimas ADPI Sains dan Teknologi, 2020)
The Covid19 pandemic that hit the world at the beginning of 2020 has paralyzed the economic sector. Tourism is the earliest sector affected, with the policy of large-scale social restrictions that make the Tourism Industry suspended. Hospitality and travel businesses lost more than 50% of their income to almost out of business. Breakthroughs and innovations are needed to stay afloat from covid hurricane 19. This writing aims to find alternatives to re-increase public interest to return to safe tourism activities without violating WHO health protocols. The method used is a qualitative method based on observations and observations, the outcome of this activity is in the form of a prototype signage and a tourism catalog that can be applied directly to the tourism industry. Conclusions while the tourism industry can still be run as long as it can meet safe health protocols in the new normal approach.